Activities of Public and Political Actors to Preserve Monuments of Industrial Heritage of Sverdlovsk Region in 1960—1980s - E. S. Lakhtionova (Научный диалог, 2022)
The activity of the inhabitants of the Sverdlovsk region in identifying, studying and preserving the monuments of the industrial past is considered. The author limits the chronology of the study to the 1960s—1980s, when objects of the industrial past of the country were also affected in the framework of security activities in relation to the historical and cultural heritage. The material for the study was both archival documents stored in the Center for Documentation of Public Organizations of the Sverdlovsk Region (Yekaterinburg) and published sources. The relevance of the study is due to the fact that the activity to preserve the industrial heritage in the Sverdlovsk region has not yet been sufficiently developed, so the study of previous experience may be useful for intensifying this type of activity now. The scientific novelty lies in the fact that for the first time on the material of the Sverdlovsk region an attempt is made to analyze all aspects of security activities in relation to industrial heritage monuments. The author distinguished and considered six directions of this activity on specific examples, the most successful of which turned out to be the direction of identifying monuments of the industrial past and putting them on state records. The reasons for the subsequent stop of activities to identify, study and preserve industrial monuments are indicated.